2016
DOI: 10.1007/s00284-016-1175-9
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Genome Sequencing of a Novel Pseudoalteromonas Phage PH1

Abstract: The family Pseudoalteromonas is highly adaptable to dissimilar ecological habitats and plays an important ecological role in the marine environment. In this study, a new Pseudoalteromonas phage PH1 was isolated from the Yellow Sea. To better understand the bacteriophage, its biological properties, including morphology, host range, growth phenotype, thermal and pH stability, and nucleic acid composition, were investigated in detail. The result showed that the phage PH1 is a Podoviridae-phage with an icosahedral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…(Table S3 and S4). Functional annotation of predicted ORFs in the NCBI non-redundant protein database showed that only 72 (29.15%) were assigned to specific functions in S-N03 (E-value < 10 −5 ), while the rest 175 (70.85%) were predicted to encode hypothetical proteins, due to incomplete genomic information of the cyanophage in database [69]. Similarly, 70 (28.46%) predicted ORFs were assigned to specific functions in S-H34, while the rest 176 (71.54%) were predicted to encode hypothetical proteins.…”
Section: General Genomic Featuresmentioning
confidence: 99%
“…(Table S3 and S4). Functional annotation of predicted ORFs in the NCBI non-redundant protein database showed that only 72 (29.15%) were assigned to specific functions in S-N03 (E-value < 10 −5 ), while the rest 175 (70.85%) were predicted to encode hypothetical proteins, due to incomplete genomic information of the cyanophage in database [69]. Similarly, 70 (28.46%) predicted ORFs were assigned to specific functions in S-H34, while the rest 176 (71.54%) were predicted to encode hypothetical proteins.…”
Section: General Genomic Featuresmentioning
confidence: 99%
“…Next, 1 µL of the ultra-purified phage (remaining samples could be stored directly at 4 • C) was dropped onto a grid surface, 2% uranyl acetate negative staining was undertaken, and then the excess staining solution was immediately removed. Phage morphology was then examined under a 100 kV transmission electron microscope (Hitachi H-7650, Tokyo, Japan) [18].…”
Section: Transmission Electron Microscopymentioning
confidence: 99%
“…The supernatant was discarded, and the precipitate was washed twice using PBS and then suspended in 30 mL of BG11 medium; this was then incubated in a lighted incubator. Samples were collected at 0, 6,12,18,24,30,36,42,48,54,60,66, and 72 h. All of the 1 mL samples were centrifuged (6000 g, 10 min) and filtered (using 0.45 µm and 0.22 µm filters), and titration was undertaken using the double-layer agar plate method. The burst size was calculated as the ratio of the number of free phages at the end of the logarithmic period to the number of infected host cyanobacteria cells at the beginning of the latent period.…”
Section: One-step Growth Curvementioning
confidence: 99%
See 2 more Smart Citations